Intervensi Keperawatan pada Pasien Terkonfirmasi COVID-19 dengan Komorbid DM Tipe 2 dan Hipertensi: Studi Kasus - Alif Khanifudin; Arifin Triyanto; Dwi Asih Rohmawati (Jurnal Sehat Mandiri, 2021)
Comorbidities in COVID-19 patients with the highest percentage are hypertension and diabetes mellitus. Patients with comorbid hypertension and DM have high morbidity and mortality. This study aims to determine the interventions in COVID-19 patients with comorbid DM and hypertension. The method used is a case study with data collection through patient and family interviews, medical record studies and direct observation or through CCTV. The studies showed that the patient was diagnosed with severe COVID-19 by oxygen therapy (NRM 15 L/min), treating COVID-19 and managing comorbid hypertension and DM with medication and monitoring and reducing anxiety. During treatment, the patient was desaturated, blood pressure and blood sugar level had not been controlled, and the anxiety was quite high. It can be said that interventions that can be given to COVID-19 patients with comorbid hypertension and DM are oxygen therapy, medication, anxiety reduction, and comorbid management. Comorbid hypertension and DM were controlled with medication and regular monitoring. the patient's blood pressure and blood sugar level had not been controlled, it is possible that the patient's anxiety is still experienced. So that as health workers in providing care are expected to pay attention to the biopsychosociospiritual aspects so that the patient's problems are resolved.